Mengembangkan Keterampilan Literasi Dasar Dengan Kebun Huruf - Putri, Julianti; Agnesa, Oki Sandra; Satir, Muhammad (LPPM IAIN Sorong, 2024)
In the province of West Papua, there are four districts that are the main focus in improving literacy skills. One of them is Raja Ampat district which is in the 4th position for low literacy rates with a population distribution in the Regency with a population distribution in Raja Ampat district spread across 24 Districts/Sub-districts with 6 Districts having a density above 45.80 people/km2. In this study, the researcher focused on one of the areas in the South Misool district, namely Dabatan village. Dabatan village is one of the villages located on the coast in the South Misool district, Raja Ampat district, West Papua province. Interactive literacy learning for elementary school children to instill early foundations is very necessary because it will improve the various competencies that children must have. The learning process for elementary school children is very important so that in the process of implementing KKN-T, researchers launched a literacy class program in order to foster children's interest in reading, the application of which is not only in school but also outside school. Of the several existing methods, the learning while playing method is the method that most increases children's interest in reading. In this case, the method used is reading while singing using the letter garden and writing letters using the 4-line method. Literacy classes are held once a week, namely on Saturdays, the place is adjusted to the comfort of the students. The implementation method applied in this literacy class is the concept of playing while learning. This method was chosen by looking at the need to handle the lack of basic literacy skills. The participants involved in this activity were elementary school children of SD Negeri 23 Dabatan